Are we progressing towards elimination of diphtheria, pertusis, tetanus from Nepal? - Jha, N; Kumar, S (Kathmandu University Medical Journal, 2009)
Diphtheria, Pertussis and Tetanus (DPT) are the vaccine preventable diseases of childhood. The published literatures and reports related to DPT immunization coverage are relatively more than DPT diseases. The striking reduction in deaths and in the incidence of these diseases has been closely associated with the introduction of specific vaccination program. Expanded Program on Immunization (EPI) is a priority program in the country. Nepal has been running country-wide immunization program since 1989. However, there is no doubt that the program has contributed significantly towards reduction of infants and child mortality. Effective and efficient surveillance system and strengthening the routine immunization against DPT are the key steps for elimination of DPT diseases. Key words: DPT, Diphtheria, Pertussis, Tetanus, Immunization, DPT Vaccine, surveillance, vaccine coverage, Nepal.   doi: 10.3126/kumj.v6i4.1749     Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 520-525